Sensitivity of Neisseria gonorrhoeae to spectinomycin and thiamphenicol. Issue 4 (August 1980) - Grunder, K; Petzoldt, D
Abstract : Between 1966 and 1978 the sensitivities of strains of Neisseria gonorrhoeae (70-80 strains in each year) to penicillin, thiamphenicol, and spectinomycin were tested. For penicillin the proportion of less sensitive strains increased from 21% in 1976 to 41% in 1978 and for thiamphenicol from 10% to 18% over the same period. All the strains proved to be sensitive to spectinomycin. A significant correlation in the degree of sensitivity was observed between penicillin and thiamphenicol but not between penicillin and spectinomycin.